(untitled) (FORUM: University of Edinburgh Postgraduate Journal of Culture & the Arts, 2014)
Addressing the negotiation of fame by the celebrity-author, and treating authorial persona as a collectively inscribed discursive identity-text, this article examines Martin Amis’s Experience (2000) for the textual strategies used to position Amis as implied editor and to emphasise the postmodern textuality of the life being narrated.